(untitled) (Studia austriaca, 2012)
Arthur Schnitzler’s Leutnant Gustl is regarded as the first instance of interior monologue in German-language literature. According to the general opinion, Edouard Dujardin, who is widely regarded as the “inventor” of the interior monologue, gave Schnitzler the narratological inspiration for his famous text. But, as will be shown by the following comparative analysis, Knut Hamsun’s novel Hunger plays, in fact, a significant role in the development of the interior monologue in the literature around the turn of the century, especially thanks to its narrative techniques.